MODIFIKASI SIFAT PLASTISITAS TANAH LEMPUNG DENGAN PENAMBAHAN PASIR: MODIFIKASI SIFAT PLASTISITAS TANAH LEMPUNG DENGAN PENAMBAHAN PASIR - Alfian Adie Chandra (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2023)
Clay soil is a type of fine-grained soil and spread many areas in Indonesia, especially Papua province. Clay soil has the plasticity characteristic where it can changes in texture and even volume influence of changes water content. Clay contains several types of minerals but the montmorillonite causes clay have the ability to absorb and seem store water longer than other soil types. The high plasticity characteristic of clay soil is the reason why this type of soil has the ability to experience volume changes such as swelling during the rainy season and shrinking during the dry season. This condition is one of the causes of clay soil having a low carrying capacity when the rainy season or when the water content contained high, so it often causes subsidence in roads or buildings. Montmorillonite content in clay can be reduced and the texture and size of very small grains can be changed by adding other materials. In this study by adding sand material with a composition 10%, 20% and 30% to the weight of clay in the original condition. Tests to determine changes in the plasticity of clay are soil properties, liquid limit, plastic limit which all of these tests refer to the applicable SNI tests and are carried out at the Civil Engineering Laboratory, Faculty of Engineering, Cenderawasih University. The data from the test results above will be used to see changes in the characteristics of clay soil, both in terms of grain size gradations and plasticity properties.